Distribuição, riqueza e endemismo de Convolvulaceae Juss. na Cadeia do Espinhaço (lato sensu) - ALVES, Joilson Viana (2022)
The Espinhaço Range occupies part of the territories of Bahia and Minas Gerais in the form of an imposing massif that is oriented in general north-south directions. Along its extension, the domains that surround it exert a strong climatic influence which, in association with the high altitudes, provide favorable conditions for the high richness and diversity of endemic species recognized among the most varied plant groups. Convolvulaceae has a cosmopolitan distribution, where the greatest richness and diversity of species are recorded in tropical regions. In this work we seek to understand the biogeography of Convolvulaceae in the Espinhaço Range, which is an area of high endemism in Brazil. To achieve the proposed objectives, a database composed of about 2,600 occurrence records compiled from SpeciesLink and Reflora was analyzed. One hundred and eighty-six species were recorded for the Espinhaço Range, of which 19 are endemic. The species were categorized into four distribution patterns: continuous, disjunct, centered on the Bahian portion and centered on the Minas Gerais portion. These patterns are determined by the environmental influences of the surrounding domains, the geology, ecological and hydrographic barriers of the Espinhaço Range. The Parsimony Analysis of Endemism pointed out two main centers of endemism promoted by climate oscillations in the past: one in the Planalto Diamantina and the other in the Chapada Diamantina. The floristic similarity analysis also showed two main groups, one in each portion, however, with low similarity between them. The richness and diversity are concentrated in the Iron Quadrangle and mainly in the Chapada Diamantina. The Middle Domain Effect assumes that species richness is higher at intermediate elevations, this is a model that applies very well to the richness of Convolvulaceae in the altitudinal gradient of the Espinhaço Range. This work is important to support the elaboration of public policies for the conservation of taxa and the Espinhaço Range.